Peran Kebijakan Dividen sebagai Mediator Pengaruh EPS, ROE, dan DER pada Return Saham - Annisa Destiara; Victor Prasetya; Dian Murdianingsih (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the role of dividend policy as a mediator in the influence of Earnings Per Share (EPS), Return on Equity (ROE), and Debt to Equity Ratio (DER) on stock returns in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Sample collection was carried out using the purposive sampling method, and 80 observation data were obtained from the company's annual financial reports. Data analysis was carried out with the help of SPSS version 25 software, which includes the t-test, Sobel test, and classical assumption testing to test the validity of the model. The results of the study indicate that partially ROE and dividend policy have a significant effect on stock returns, while EPS and DER do not have a significant effect. In addition, dividend policy is not proven to be a mediator in the relationship between EPS, ROE, and DER on stock returns. These findings suggest that investors need to consider profitability and dividend policy more than capital structure when making investment decisions.